Evidence of the Development of Pedagogical Content Knowledge Related to Chemical Bonding during a Course for Preservice Chemistry Teachers - Roko Vladušić; Robert Bucat; Mia Ožić (Center for Educational Policy Studies Journal)
The impression that many preservice chemistry teachers demonstrate issues in the application of their pedagogical content knowledge in teaching practice, especially in the area of fundamental chemistry topics, served as motivation for changes to the Chemistry Education 2 course curriculum. In order to stimulate pedagogical content knowledge, the course has been changed in the following areas: intending learning outcomes, the language of chemistry instruction, awareness of “Johnstone’s triangle” of operations, and common alternative conceptions. To obtain evidence of preservice teachers’ in-practice pedagogical content knowledge about chemical bonding, especially pedagogical content knowledge related to the revised areas of the Chemistry Education 2 course, we designed and conducted a case study based on detailed monitoring of one preservice teacher’s pre-teaching, teaching and teaching evaluation activities. The findings demonstrate evidence of growth of the preservice teacher’s pedagogical content knowledge of chemical bonding, with particular characteristics indicating that the source of this growth is almost certainly the revised Chemistry Education 2 curriculum.